2014
DOI: 10.5130/opm.v1i1.3949
|View full text |Cite
|
Sign up to set email alerts
|

Project manager insights: An analysis of career progression

Abstract: The project manager is key to the success of any project. But the path to becoming a successful project manager is ill defined. In this study, the authors analyzed interview results of 87 project managers' responses to questions associated with entry into the field, career progression, and advice for the new project manager, seeking to better understand practicing project manager career progression. Qualitative analysis techniques were used to identify recurring themes from the interview summaries. The themes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
(24 reference statements)
0
17
1
1
Order By: Relevance
“…As for the individual side of employability enhancement, contrary to the arguments we provided (Hobfoll, 1989; 2002), according to the available evidence (De Vos & Soens, 2008), as well as insights from the project management literature (Marion et al, 2014), employability was not associated with subjective and objective career success. This is somewhat surprising and implies that employability, as an individual resource that individuals can nurture and develop, plays no role in increasing project managers’ career success.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…As for the individual side of employability enhancement, contrary to the arguments we provided (Hobfoll, 1989; 2002), according to the available evidence (De Vos & Soens, 2008), as well as insights from the project management literature (Marion et al, 2014), employability was not associated with subjective and objective career success. This is somewhat surprising and implies that employability, as an individual resource that individuals can nurture and develop, plays no role in increasing project managers’ career success.…”
Section: Discussioncontrasting
confidence: 58%
“…These relationships can support knowledge exchange and development and may be helpful with future career progressions and project assignments. Marion et al (2014), analyzing the interviews of 87 project managers, found self-improvement as a core theme in their discourse. In particular, they found that project managers were particularly keen in improving themselves over the course of their careers by taking an active role in preparing themselves for future assignments and projects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this analysis, two themes observed from "Project Manager Insights: An Analysis of Career Progression" (Marion, Richardson, & Earnhardt, 2014) were further analyzed to better understand the following:…”
Section: Discussionmentioning
confidence: 99%
“…Rarely does a project management career begin within the profession. The typical project management career follows as a consequence of another career within the industry (Marion, Richardson, & Earnhardt, 2014). How well do we understand these entry routes?…”
Section: Full Papers Must Be Submitted By 28 February 2018mentioning
confidence: 99%